The Composition and Concordance of Lactobacillus Populations of Infant Gut and the Corresponding Breast-Milk and Maternal Gut - Zhang, Xuyao; Mushajiang, Saiyidan; Luo, Baolong; Tian, Fengwei; Ni, Yongqing; Yan, Wenli (Frontiers in Microbiology, 2020)
The maternal gut is the principal source of commensal bacteria in the infant gut during the lactation stage, where breast milk acts as an intermediary for the transfer of potential probiotic bacteria consortia, including Lactobacillus. This study aimed to characterize the bacterial communities in human milk, maternal and infant feces in a small yet very homogeneous cohort of 25 healthy mother-infant pairs in northwestern China (n=25, infant age from 7 days to 2 years), with special emphasis on the cooccurrence and vertical transfer of Lactobacillus phylotypes at the species or strain level in mother-breast milk-infant triads. Accurate sequencing analysis revealed that among 73 Lactobacillus zero-radius operational classification units (ZOTUs) identified, 58 belonging to 18 recognized species or species groups were distributed in all three types of samples. Lactobacillus ruminis, L. mucosae and L. gasseri-johnsonii as true residents were the most represented in all three ecosystems, whereas the content of Lactobacillus phylotypes commonly developed as probiotics was not dominant. While the numbers of Lactobacillus species in breast milk and infant feces were greater than that in maternal feces, principal coordinates analysis (PCoA) based on beta diversity, coupled with the frequency of isolates determined by culture methods, showed that the Lactobacillus community in the infant gut was more similar to that in the maternal gut than to that in breast milk, suggesting that the gut is niche selective for Lactobacillus populations. In addition, identical strains of L. ruminis, L. paracasei, L. mucosae and L. salivarius were isolated from multiple mother-infant pairs, supporting the hypothesis that vertical transfer of bacteria via breastfeeding contributes to the initial establishment of the microbiota in the developing infant intestine.